Exploring the Strategies, Utilisation and Limitations of Digital Tool Adoption in Sugarcane Farming (Indian Journal of Extension Education, 2025)
The study investigates how sugarcane farmers are currently using digital technologies, identifies the obstacles to their efficient use, and suggests ways to improve the digitalization of sugarcane farming methods. The research was carried out during 2024 in Deoria (district) Sugarcane Committee’s Jaura Bazar centre “A”, Uttar Pradesh, which is the Deoria Sugarcane Committee’s highest-producing sugarcane centre. Purposive sampling was used to choose the sugarcane committee and centre, while random sampling method was used to select the villages and respondent farmers. Garrett’s ranking approach was used to assess the constraints of digital tools and technology as perceived by sugarcane cultivators. Data was collected from 230 respondents using a pre-structured interview schedule, revealing that mobile applications are mostly used for seed treatment and pest control in sugarcane farming, and they are less frequently used for other tasks. The primary barriers include technological challenges, budgetary limitations, and societal concerns. It is suggested to use strategies like offline apps, training, free subscriptions, and local language assistance to boost acceptability.